Identifying long-term stable refugia for dominant Castanopsis species of evergreen broad-leaved forests in East Asia: A tool for ensuring their conservation. (September 2022) - Tang, Cindy Q.; Matsui, Tetsuya; Ohashi, Haruka; Nualart, Neus; Herrando-Moraira, Sonia; Dong, Yi-Fei; Grote, Paul J.; Van Ngoc, Nguyen; Van Sam, Hoang; Li, Shuaifeng; Han, Peng-Bin; Shen, Li-Qin; et al.
Abstract: Identifying and protecting refugia is a priority for conservation management under projected anthropogenic climate change. We have two main objectives: the first is to explore the spatial (East Asia) and temporal (Last Glacial Maximum to year 2070) distribution patterns of dominant Castanopsis species of evergreen broad-leaved forests, also the relation with their niche breadths; the second is to identify long-term stable refugia for preserving these species and provide a framework of conservation strategies. We find that there is an extraordinary richness with 32 dominant Castanopsis species, and they form both a geographically and climatically almost unbroken connection from ca. 5°N to 38°N, having thus ecological significance. During the Mid-Holocene and, particularly, the Last Glacial Maximum, the predicted suitable areas of the species as a whole were larger than those in the present. By 2070, potentially suitable areas with high richness of dominant Castanopsis species will be reduced by 94.5 % on average. No correlation between species niche breadths and distribution ranges is found, which could be due to regional climate stability. Mountains of southwestern and southern Yunnan in China are identified as climatically long-term stable refugia for 7–9 Castanopsis species. We recommend that these refugia have the highest priority of conservation to prevent their extinction. Our suggested urgent measures include improving the effectiveness of currently protected Castanopsis species and expanding the network of protected areas to cover a larger fraction of the refugia, as well as ensuring Castanopsis species natural regeneration potential in fragmented and natural secondary forest areas.